Coopetition in the furniture industry cluster versus competitiveness and innovations of selected companies within the cluster - Janusz Kroik; Adam Świda (Economic and Environmental Studies (E&ES), 2018)
The paper analyses the phenomenon of coopetition in the conditions of a large cluster of companies from the furniture industry in the vicinity of K\~nepno. It covers a two-stage analysis. The first stage defines the general characteristics of the coopetition potential for the cluster on the basis of the authors' previous research. In this respect, the methodology of J. Cygler was used. At the second stage, using the case study approach, three companies of different market and assets potential were assessed in detail. The study proved that, when assessing the character of business relations at the level of the furniture production cluster, particular entities can be classified in different categories of use in business practice, covering innovations in coopetition relations.
Keywords: L14; L29; L69; D21; 330; cluster coopetition; enterprise; reviews; innovation activities; competence assumptions